BURNING TIMES OF VOLATILES FROM TURKISH COALS DURING FLUIDIZED-BED COMBUSTION - (:unkn) unknown (BUTTERWORTH-HEINEMANN LTD, 1994)
The burning times of the volatiles from twelve Turkish coals ranging from bituminous to lignite was experimentally investigated in a bench-scale atmospheric fluidized bed combustor. Devolatilization time was determined by visual observation of the plume-like volatiles flame. The time lapse between the appearance and disappearance of this flame was recorded as flame extinction time. The effects of particle size (1.0-11.2 mm) and bed temperature (650-920-degrees-C) were investigated, and the effect of moisture was determined by measurements on oven-dried samples. Fragmentation was observed for a few coals after devolatilization was virtually complete, but the majority preserved their original particle shape. Flame extinction times were related to initial particle diameter by a power law; numerical constants for this relation were determined for each coal by regression analysis. Two parameters - volatile matter/fixed carbon ratio and volatile matter heating value - are proposed to characterize the effect of coal type on devolatilization time. The observed effects of particle size, bed temperature, moisture pore structure and coal type on flame extinction time are consistent with heat transfer to and in the coal particle as the rate-controlling step.
Keywords: DEVOLATILIZATION; FLUIDIZED BEDS; COMBUSTION; DEVOLATILIZATION; PARTICLES; MODEL